Weed Management in Pastures and Rangeland - 2009 - Brent A. Sellers; Jason A. Ferrell; J. Tredaway Ducar (EDIS)
Revised! SS-AGR-08, a 13-page fact sheet by B.A. Sellers and J.A. Ferrell, describes mechanical control, sanitation, chemical control, postemergence applications, and precautions to take when using phenoxy or benzoic acid herbicides. Published by the UF Department of Agronomy, January 2009.